PERSYARATAN LABORATORIUM LINGKUNGAN DAN KONDISINYA DI INDONESIA - Kardono, Kardono (Jurnal Teknologi Lingkungan, 2008)
The level of environmental quality is indicated by how much the pollutants enter into and stay in it, that is whether they are still below or already above the regulated pollutants standard. In knowing pollutant concentration in the environment, pollutantmeasurement must be done by employing appropriate instrument and using qualified/ certified operator. Therefore, the role of environmental laboratory is crucial in preparing instrumentation, operator, as well as standard operating procedure (SOP) in order for sampling and analysis of pollutants to work properly and result qualified data. This type of laboratory is strongly determined by how the laboratory is operated with the standard mechanism, called good laboratory practice (GLP). GLP will be met by the laboratory that owns the current state of the art instrumentation, capability and experience of the operator/analyst in conducting sampling and analysis, availability of SOP, capability to control thequality (Quality Control) and to assure the quality (Quality Assurance) of its work and the results. Some of laboratory in Indonesia has received certification from National Committee on Acreditation (KAN). However, the granted certification from the KAN must be first checked whether it is for all or part of the laboratory capabilities. Second, whether during the analysis it is already checked the accuracy and preciseness of the instrument employed. Unlike in developed countries, this type of such check has not so far been done in Indonesia. In term of QualityAssurance, the institution that grants the laboratory certification, for example KAN in Indonesia, will send blind samples to targeted laboratory to analyze how much the concentration of certain pollutants detected by this laboratory. Third, whether the operators have strongly followed the existing SOP. Thus, in order to operate laboratory in a right procedure and accuracy, a lot of work must be done carefully in order to result a qualified data. This paper is going to describe and to evaluate how the environmental laboratory is operated and how their condition in Indonesia.